2010
DOI: 10.1007/s11325-010-0346-3
|View full text |Cite
|
Sign up to set email alerts
|

Does sleep apnea increase the risk of cardiorespiratory complications during endoscopy procedures?

Abstract: For patients undergoing endoscopy procedures under conscious sedation, the presence of OSA does not clearly increase the risk of cardiorespiratory complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…Despite this logic, hypoxic events as well as other adverse outcomes do not seem to occur more frequently in patients with OSA (Table 1). [10][11][12][13][14] In the present study, conscious sedation requirements and procedure length did not vary significantly between patients with and without OSA. Variations in cardiopulmonary parameters during endoscopy with conscious sedation were common in both groups but did not result in any significant clinical sequelae, even after a 30-day chart review for adverse events.…”
Section: Discussionsupporting
confidence: 42%
“…Despite this logic, hypoxic events as well as other adverse outcomes do not seem to occur more frequently in patients with OSA (Table 1). [10][11][12][13][14] In the present study, conscious sedation requirements and procedure length did not vary significantly between patients with and without OSA. Variations in cardiopulmonary parameters during endoscopy with conscious sedation were common in both groups but did not result in any significant clinical sequelae, even after a 30-day chart review for adverse events.…”
Section: Discussionsupporting
confidence: 42%
“…With respect to studies involving a polysomnographic diagnosis, Mador [10] did not find a higher number of complications in patients with OSAS, regardless of the cutoff for diagnosis of OSAS or its severity. However, polysomnography was performed before endoscopy in only 63.5% of cases and preceded the procedure by a median of 1.84 years.…”
mentioning
confidence: 78%
“…Furthermore, it is not clearly established what constitutes an adequate oxygen flow and how protocols for the administration of oxygen should change in the presence of comorbidities such as obesity. Mador and colleagues [10] add to our understanding with their study demonstrating that the increased oxygen flow of 4 L/min in obese patients reduces the number of desaturations.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In a prospective study that screened patients (n = 904) for OSA risk prior to endoscopic procedures requiring conscious sedation, no difference was found in complication rates by OSA risk stratification [82]. Additional retrospective studies totaling over 2100 endoscopic procedures under conscious sedation reported no increase in intra-or postprocedural adverse events in patients with objectively confirmed OSA compared to controls [83][84][85][86]. And in a small prospective case-control study of patients with PSGconfirmed OSA (n = 31) undergoing colonoscopy, there were no differences in the rates of adverse events despite higher midazolam dosing and deeper sedation in the OSA patients [87].…”
Section: Procedures With Conscious Sedationmentioning
confidence: 99%